Handbook of epidemiology - Ahrens, Wolfgang (Springer New York, 2014)
This 5-volume reference covers the entire field of epidemiology, from statistical methods and study design, to specialized areas such as molecular epidemiology, and applications in clinical medicine and health services research. This updated edition of the Handbook of  Epidemiology adds 20 new chapters on: History of Epidemiological Methods and Concepts, Cluster Randomized Trials, Internet-Based Epidemiology, Misclassification, Sensitivity Analysis and Bias Analysis,  Emergency and Disaster Health Surveillance, Statistical Inference, Data Management in Epidemiology, Bayesian Methods in Epidemiology, Generalized Estimating Equations, Directed Acyclic Graphs, Life Course Epidemiology, Physical Activity Epidemiology, Radiation Epidemiology, Epidemiology of  Obesity, Epidemiology of Respiratory Allergies and Asthma, Epidemiology of  Dental Diseases, Epidemiology of Digestive Diseases, Epidemiology of Psychiatric Disorders, Epidemiology of  Diabetes. All other chapters are extensively revised from  the 1st edition. This is a reference for epidemiological researchers and graduate students in public health.